Efficacy of bendamustine and rituximab in splenic marginal zone lymphoma: results from the phase II BRISMA/IELSG36 study. (8th November 2018) - Iannitto, Emilio; Bellei, Monica; Amorim, Sandy; Ferreri, Andrés J. M.; Marcheselli, Luigi; Cesaretti, Marina; Haioun, Corinne; Mancuso, Salvatrice; Bouabdallah, Krimo; Gressin, Remy; Tripodo, Claudio; Traverse‐Glehen, Alexandra; et al.
Summary: Splenectomy in addition to immunotherapy with rituximab can provide quick and sometimes durable disease control in patients with splenic marginal zone lymphoma (SMZL). However, systemic chemotherapy is ultimately required in many cases. The BRISMA (Bendamustine‐rituximab as first‐line treatment of splenic marginal zone lymphoma)/IELSG (International Extranodal Lymphoma Study Group)36 trial is an open‐label, single arm phase II study designed by the IELSG in cooperation with the Fondazione Italiana Linfomi and the lymphoma Study Association according to Simon's two‐stage method. The primary endpoint was complete response rate. Fifty‐six patients with SMZL diagnosis confirmed on central revision were treated with bendamustine (90 mg/m 2 days 1, 2) and rituximab (375 mg/m 2 day 1) every 28 days for six cycles (B‐R). The overall response and CR rates were 91% and 73%, respectively. Duration of response, progression‐free survival and overall survival at 3 years were 93% (95% confidence interval [CI] 81–98), 90% (95% CI 77–96) and 96% (95% CI 84–98), respectively. Toxicity was mostly haematological. Neutropenia grade ≥3 was recorded in 43% of patients; infections and febrile neutropenia in 5·4% and 3·6%. Overall, 14 patients (25%) experienced serious adverse events. Five patients (9%) went off‐study because of toxicity and one patient died from infection. In conclusion, B‐R resulted in a very effective first‐line regimen for SMZL. Based on the results achieved in the BRISMA trial, B‐R should be considered when a chemotherapy combination with rituximab is deemed necessary for symptomatic SMZL patients.